Development of Augmented Reality-Based Learning Multimedia on Volcanism to Enhance Visualization of Abstract Concepts in Senior High School - Salsabila, Salsabila; Farizal, Farizal (SYNAPSI: Journal of Information Systems and Informatics Education, 2026)
Purpose of the study: This study aims to develop Android-based Augmented Reality (AR) learning multimedia for volcanism material in senior high school by integrating three-dimensional models of volcano internal structures and testing its feasibility as a learning medium. Methodology: This research applied a Research and Development (R&D) method using a modified Borg & Gall model with eight stages. The product was developed using Unity 3D 2018.4.4f1, Vuforia SDK, and Blender 2.79b. The subjects included one media expert, two material experts, and 20 students of class X IPS 1 at SMA N 1 Ngaglik. Data collection used observation and questionnaires with a Likert scale, analyzed through descriptive quantitative methods. Main Findings: Validation results showed a score of 71 from the media expert (Very Feasible), 146 from material experts (Very Feasible), and 1483 from student responses (Feasible). Black box testing indicated all features and navigation buttons functioned properly. The multimedia contains six main menus and five sub-materials supported by AR pages displaying 3D volcano-related objects, including magma intrusion, magma extrusion, volcano morphology, and eruption types. Novelty/Originality of this study: The novelty of this study lies in integrating portable Android-based AR multimedia with 3D visualization of volcano internal structures without requiring special infrastructure such as projectors or Kinect sensors, making it more practical for senior high school learning compared to previous studies.